Animals in relation to land use - Butterworth, M.H. (Elsevier, 1984)
Discusses issues related to land use with particular reference to rangeland and to land used for extensive or semi-extensive grazing, describing the world distribution of grazing lands, the problem of overgrazing; and practices useful in the improvement of grazing land.